HETEROTOPIC PREGNANCY WITH SUCCESSFUL PREGNANCY OUTCOME: A RARE CASE REPORT - SUNIL KUMAR SAMAL,; SETU RATHOD, (International Journal of Pharma and Bio Sciences, 2015)
Heterotopic pregnancy (HP), the presence of two gestational sacs simultaneously, is a rare event, but with the advent of assisted reproductive technology (ART), it is now an increasingly common complication. We report a case of a 35-year-old G2A1 who was presented to our casualty at 13 weeks gestation with complains of severe pain abdomen and features of hypovolemic shock. Subsequently, she was diagnosed as a case of HP with right ruptured rudimentary horn pregnancy and viable intrauterine pregnancy of 13 weeks gestation. Emergency laparotomy with resection of right side rudimentary horn of uterus was done and the viable intrauterine gestation was allowed to continue. The course of intrauterine pregnancy was uneventful and she delivered a term female by caesarean section for non progress of labour.